Analisis Manajemen Risiko Keuangan Industri dengan Tinjauan Evaluasi Total Productive Maintenance Studi Kasus di PT ABC - Aldi Adi Pratama (Universitas Katolik Musi Charitas, 2022)
PT ABC revenue system in competing with competitors as a global fertilizer supplier, has led to a shift to focus on higher sales levels. Based on the review Total Productive Maintenance , the researcher found that the level of loss from the burden of repairing the operational costs of the APPO machine affects the level of company profitability. Due to damage to the blades and filters the engine creates a discharge load in the short term. The company must emphasize supervision with a minimum standard limit of MTBF, MTTR, and MDT figures for each type of damage. Namely, the broken blade resulted in MTBF of days, MTTR of 30 minutes and MDT of 32 minutes, while the filter was damaged with results of MTBF of 9 days, MTTR of 11 minutes, and MDT of 5 minutes. The damage that occurs is found to be forcing the machine's performance to be irregular and not maintained, when the production and post-production processes will be carried out. Another thing that the researcher revealed in this finding is that the amount of load on the APPO machine must be adjusted to the upper threshold limit for the raw materials to be processed. Because if this continues to happen in order to pursue sales targets and high demand, it is said that the level of machine maintenance losses will dominate profits, as well as sales profits.